Urgent Need for Reduction in Greenhouse Gas Emissions in Industrial Processes: Are We Past the Tipping Point for Global Warming? - Piacentini, Ruben Dario Narciso (2013)
In a previous Guest Editorial (Piacentini and Mujumdar, 2007) and an article (Piacentini and Mujumdar, 2009), we analyzed the relation between climate change and industrial processes, mainly related to drying.